Development of Digital Teaching Materials Utilizing Flipbook Maker for Painting Art Materials In Grade IX at SMP Negeri 2 Pariaman - Pebriyeni, Eliya; Kharisma, Maltha; Aisyah, Siti; Ramadhan, Ary; Jermaina, Nina (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The emerging problem is the low learning outcomes of the students, and the teaching media used by the teacher, such as PowerPoint and videos on painting practices, are still not perceived to enhance the students' understanding. The students' lack of interest in reading printed books.This research was conducted at SMP Negeri 2 Pariaman. The goal of this study is to create digital teaching materials based on a flipbook maker for painting subjects at SMP Negeri 2 Pariaman and to determine the validity and practicality levels of the digital teaching materials based on a flipbook maker for painting subjects at SMP Negeri 2 Pariaman. The research methodology uses a research and development (R&D) design, which is a study that systematically designs and develops it. The ADDIE model, which stands for assess, design, develop, implement, and evaluate, is used in the instructional design methodology. The data collection technique in this study involved interviews, documentation, and questionnaires. The results of the material validation obtained scores of 83.7%, design expert 85.4%, and language expert 85.3%, all categorized as very valid. The results conclude that the digital teaching materials are suitable for being tested on students of painting material at SMPN 2 Pariaman. The results of the student questionnaire on a small scale were 85.7% and on a large scale 98.09% regarding the use of digital teaching materials in painting, which the researcher developed. It can be concluded that these digital teaching materials received good results, making them practical and appropriate for use in the visual arts education process, specifically in painting.